Spark-plasma-sintering (SPS) of nanostructured and submicron titanium oxide powders - Angerer, P. (2012)
Spark-plasma-sintering (SPS) consolidation of submicron and nanostructured titanium oxide (TiO2) powders was performed between 800 and 1000 °C for 1 min. The results were compared with conventional sintering using electrical resistant furnace that was performed between 600 and 1000 °C for 120 min. The compacted samples were investigated by X-ray diffraction (XRD) and scanning electron microscopy (SEM). This investigation clearly shows that the SPS method is capable of obtaining samples with high densities and corresponding fine grain-size from nanostructured raw TiO2 powder. Remarkable difference in the sintering techniques was observed in samples with >95% theoretical density where the relative grain growth quotient d/do for the 40 nm powder was ∼3 when SPS was employed while the value obtained for conventional sintering was ∼26.